2020
DOI: 10.1007/s00167-020-06359-w
|View full text |Cite
|
Sign up to set email alerts
|

Lateral unicompartmental knee arthroplasty is a safe procedure for post-traumatic osteoarthritis after lateral tibial plateau fracture: a case–control study at 10-year follow-up

Abstract: Purpose Very few studies focus on lateral unicompartmental arthroplasty (LUKA) in the setting of post-traumatic osteoarthritis (PTOA). The hypothesis of our study is that LUKA is an efective procedure for isolated lateral PTOA with similar outcomes to non-traumatic LUKA. Methods Between 1990 and 2016, eighteen LUKA performed for isolated lateral tibiofemoral osteoarthritis secondary to tibial plateau fracture were retrospectively reviewed (post-traumatic group) and matched with a control group of thirty-six LU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Data from 32 studies were available to compare mobile-bearing vs. fixed-bearing implants; 10 studies (n ¼ 2,268) with mobile-bearing implants [14,18,28,32,33,37,38,41,50,53], 18 studies (n ¼ 1,469) with fixed-bearing [8,26,[42][43][44][45][46][47][48][49]27,30,31,[34][35][36]39,40] and 4 additional studies that reported outcomes for both (n ¼ 1,743 mobile-bearing, n ¼ 790 fixed-bearing) [25,29,46,51]. 18 studies had a moderate risk of bias [8,18,[44][45][46][47][48][49][50]53,26,31,33,34,37,39,42,…”
Section: Fixed-vs Mobile-bearing Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from 32 studies were available to compare mobile-bearing vs. fixed-bearing implants; 10 studies (n ¼ 2,268) with mobile-bearing implants [14,18,28,32,33,37,38,41,50,53], 18 studies (n ¼ 1,469) with fixed-bearing [8,26,[42][43][44][45][46][47][48][49]27,30,31,[34][35][36]39,40] and 4 additional studies that reported outcomes for both (n ¼ 1,743 mobile-bearing, n ¼ 790 fixed-bearing) [25,29,46,51]. 18 studies had a moderate risk of bias [8,18,[44][45][46][47][48][49][50]53,26,31,33,34,37,39,42,…”
Section: Fixed-vs Mobile-bearing Componentsmentioning
confidence: 99%
“…Data from 15 studies reported the use of all-PE vs. metal-backed fixedbearing implants; 5 studies (n ¼ 267) with all-PE implants [25,34,36,40,53]; 10 studies (n ¼ 660) with metal-baked implants [8,26,27,29,39,[42][43][44][45][46]. Nine studies had a moderate risk of bias [8,26,34,39,[42][43][44][45][46] and six studies had a serious risk of bias [25,27,29,30,36,40].…”
Section: All-pe Vs Metal-backed Components (Fixed-bearing)mentioning
confidence: 99%
See 1 more Smart Citation
“…Two thousand one hundred and sixty studies were then screened for eligibility based on their titles and abstracts. After a screening and retrieval process, 40 articles received a full‐text evaluation for eligibility and finally, 26 studies 7–9,15–37 were included in this meta‐analysis. Detailed information regarding study selection is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…39 Recent studies have demonstrated that primary UKA and secondary UKA for PTOA both provide excellent outcomes and have similar complication rates and long-term survivorship (>90%). 40 41…”
Section: Discussionmentioning
confidence: 99%